High reliability organizations : a healthcare handbook for patient safety & quality - Cynthia Oster; Jane Braaten (Indianapolis, IN : Sigma Theta Tau International, 2021)
"Patient safety and quality of care are critical concerns of healthcare consumers, payers, providers, organizations, health systems, and governments. Although a strong body of knowledge shows that high-reliability methods enable the most efficient, safe, and effective care, these methods have yet to be completely implemented across healthcare. According to authors Cynthia Oster and Jane Braaten, nurses-who are on the frontline of providing safe and effective care-are ideally situated to drive high reliability. High Reliability Organizations: A Healthcare Handbook for Patient Safety & Quality, Second Edition, equips nurses and healthcare professionals with the tools necessary to establish an error detection and prevention system. This new edition builds on the foundation of the first book with best practices, relevant exemplars, and important discussions about cultural aspects essential to sustainability. New material focuses on: High-reliability performance during a pandemic, organizational learning and tiered safety huddles, high reliability in infection prevention and ambulatory care, the emerging field of human factors engineering within healthcare, creating a virtual resource toolkit for frontline staff"-- Provided by publisher
Keywords: Corporate culture; Safety Management organization & administration; Health facilities Business management